If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 9x + -15 Reorder the terms: -1 + 7x = 9x + -15 Reorder the terms: -1 + 7x = -15 + 9x Solving -1 + 7x = -15 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -1 + 7x + -9x = -15 + 9x + -9x Combine like terms: 7x + -9x = -2x -1 + -2x = -15 + 9x + -9x Combine like terms: 9x + -9x = 0 -1 + -2x = -15 + 0 -1 + -2x = -15 Add '1' to each side of the equation. -1 + 1 + -2x = -15 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = -15 + 1 -2x = -15 + 1 Combine like terms: -15 + 1 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| X/12-46=6 | | -6u+46=6u | | x-(0.2x)=0.6 | | 5/3u=25 | | -(5X+4)-(-4X-9)=13 | | 12y^2+23y+5= | | 9v^2-30+25=0 | | 4+9k=-5 | | 6w-2=2w+58 | | 9v^2-30v-25=0 | | 8x=16/7 | | D=26/pi | | http://media1.acellus.com/Library/00001022_223_A1.gif | | 56+8m=128 | | 4y^2+17y-15= | | 14y+1=1y+27 | | n-17=-13 | | 17n-70=168 | | 8x-10=8x-6 | | 42=4x+2x | | 4a+1=1a+25 | | f(x)=0.15x+5 | | 8y-5y=27 | | 5/3x-1=6/5x | | 6(x+30)=90 | | 8z-6=58 | | 5z+5=40 | | .2x+.6y=.52*80 | | 25=X+X+6 | | 1.5(x-4)=9.2 | | Y=3/4(x-3/4) | | Y=x(x+20) |